Cost-minimization analysis of adjuvant chemotherapy regimens given to patients with colorectal cancer in Japan. Issue 1 (December 2016) - Takata, Kosuke; Fujita, Ken-ichi; Kubota, Yutaro; Ishida, Hiroo; Ichikawa, Wataru; Shimada, Ken; Sekikawa, Takashi; Taki-Takemoto, Iori; Kamei, Daisuke; Iwai, Shinichi; Sasaki, Yasutsuna
Abstract Background Consideration of medical costs as well as effectiveness and adverse events is rapidly been becoming an important factor in the selection of chemotherapy regimens. However, practical data on the costs of chemotherapy are scarce. We clinically estimated the medical costs of 6 adjuvant chemotherapy regimens for colorectal cancer on the basis of clinical and cost-related data and compared their cost-effectiveness by cost-minimization analyses. Methods All patients who received adjuvant chemotherapy for colorectal cancer between April 2012 and May 2015 at four hospitals affiliated with Showa University were studied retrospectively. Clinical and cost data related to adjuvant chemotherapy were collected from medical records and medical fee receipt data, respectively. Six adjuvant chemotherapy regimens were studied: capecitabine and oxaliplatin (CapeOX); 5-fluorouracil (5-FU), ℓ-leucovorin (LV), and oxaliplatin (modified FOLFOX6 [mFOLFOX6]); 5-FU and LV (5-FU/LV); tegafur and uracil (UFT), and LV (UFT/LV); capecitabine; and tegafur, gimeracil and oteracil (S-1). The regimens were divided into 2 groups according to whether or not they contained oxaliplatin because of the difference in effectiveness. Cost-minimization analyses, where relative costs of regimens showing equivalent effectiveness were simply compared, were performed to evaluate the cost-effectiveness of the regimens in each group. Results A total of 154 patients with colorectal cancer received adjuvant chemotherapy during the study period. Fifty-seven patients were treated with CapeOX, 10 with mFOLFOX6, 38 with UFT/LV, 20 with capecitabine, and 29 with S-1. No patient received 5-FU/LV. The total costs of oxaliplatin-containing regimens were significantly higher than those of oxaliplatin non-containing regimens. The high cost of oxaliplatin, but not the costs of drugs or various tests for the treatment of adverse events, was the primary reason for the higher costs of the oxaliplatin-containing regimens. The cost-effectiveness of the oxaliplatin-containing regimens CapeOX and mFOLFOX6 were comparable. Among the oxaliplatin non-containing regimens, the cost-effectiveness of S-1 and capecitabine was superior to that of UFT/LV. Conclusion Thus, we provided the cost-effectiveness data of 5 adjuvant chemotherapy regimens for colorectal cancer based on practical clinical and cost data from Japanese patients. The results can be included as a factor in regimen selection because these results would represent the real world. Trial registration This study is a retrospective observational study and does not include any health care interventions. Therefore, we did not register the protocol of this study.